2014
DOI: 10.1371/journal.pone.0088702
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Spatial Structure on Viral Genomic Diversity Generated during Adaptation to Thermal Stress

Abstract: BackgroundMost clinical and natural microbial communities live and evolve in spatially structured environments. When changes in environmental conditions trigger evolutionary responses, spatial structure can impact the types of adaptive response and the extent to which they spread. In particular, localized competition in a spatial landscape can lead to the emergence of a larger number of different adaptive trajectories than would be found in well-mixed populations. Our goal was to determine how two levels of sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…Consistent with the majority of in vitro studies 2-4 and theoretical work 1,5,7,8 we show greater phenotypic diversification in heterogeneous potting compost compared with a more homogeneous potting compost-water mix. More importantly, we show that adaptation in the heterogeneous environment is greater than in the homogenous environment – a result that can arise theoretically 16 and is supported by some, but not all, empirical studies 3,12,17,18 – suggesting that natural spatial heterogeneity may indeed promote rapid adaptation. The latter result is particularly striking given that population sizes were approximately 3-fold lower in heterogeneous environments, which, if anything, would lead to a reduced mutation supply and less efficient selection, and hence a slower pace of adaptation 30 .…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Consistent with the majority of in vitro studies 2-4 and theoretical work 1,5,7,8 we show greater phenotypic diversification in heterogeneous potting compost compared with a more homogeneous potting compost-water mix. More importantly, we show that adaptation in the heterogeneous environment is greater than in the homogenous environment – a result that can arise theoretically 16 and is supported by some, but not all, empirical studies 3,12,17,18 – suggesting that natural spatial heterogeneity may indeed promote rapid adaptation. The latter result is particularly striking given that population sizes were approximately 3-fold lower in heterogeneous environments, which, if anything, would lead to a reduced mutation supply and less efficient selection, and hence a slower pace of adaptation 30 .…”
Section: Discussionsupporting
confidence: 74%
“…However, population structure may promote adaptive evolution by allowing greater exploration of adaptive landscapes 13,14 and spatial heterogeneity can also increase the chance that beneficial mutations will encounter an environment that maximises their fitness effect 15,16 . In vitro experimental studies involving bacteria or viruses evolving in nutrient media provide support for both views 3,12,17,18 . This variation in empirical results demonstrates the nuanced effect of in vitro experimental conditions, making it crucial to know how spatial heterogeneity impacts adaptive evolution (and indeed diversification) under ecologically relevant conditions.…”
Section: Introductionmentioning
confidence: 90%
“…There are a large number of works focused on virus adaptation to changes in temperature [32][33][34][35][36][37][38][39]. In the particular case of Qβ, studies carried out in our group showed that: (i) adaptation to 43 • C entails a fitness cost on replication at 30 • C but not at 37 • C [40], (ii) there is an influence of the standing genetic diversity and the pattern of temperature increase on the speed of adaptation [41,42], and (iii) a mutant with increased resistance to heat shocks in the extracellular medium can also adapt to replicate at 43 • C [43].…”
Section: Introductionmentioning
confidence: 99%
“…The abundance of viral gene sequences and advances in analytical methods have increased our ability to infer these processes and track viral spread [ 6 ]. Second, rapidly evolving viruses are capable of adapting swiftly to the novel environments they encounter as they spread geographically [ 7 ], with the potential to alter, for example, vector specificity or sensitivity to drugs or immune responses. Third, spatial sampling provides a common frame of reference whereby virus evolution and migration can be integrated with epidemiological data, or with environmental measurements such as humidity or land use.…”
Section: Introductionmentioning
confidence: 99%